Dynamics Of ASN Tax Compliance in the Transition of Higher Education To PTN-BH Status - Ong, William; Pusposari, Devy (West Science Accounting and Finance, 2025)
This study aims to determine the influence of tax socialization, tax sanctions, income level, and number of dependents with risk preference as a moderation variable on the compliance of ASN taxpayers at Universitas Brawijaya. This study uses convenience sampling by distributing questionnaires to 70 respondents registered at the Tax Center FEB UB. The research sample obtained was 62 respondents processed using the SmartPLS application with the SEM method. This study found that tax socialization, tax sanctions, income level, and number of dependents had no effect on the compliance of ASN taxpayers of Universitas Brawijaya. In addition, risk preferences have not been able to moderate the influence of tax socialization, tax sanctions, income levels, and the number of dependents on the compliance of ASN taxpayers at Universitas Brawijaya. The implication of this study is to find out the factors that affect the compliance of taxpayers of Universitas Brawijaya as well as the application of prospect theory and compliance theory within the scope of Universitas Brawijaya.